Familial hypercholesterolaemia with tuberous and tendinous xanthomas: case report and mutation analysis. (1st October 2015) - Kong, M.‐X.; Zhang, Q.; Cao, L.; Zhao, C.; Ru, G.‐Q.; Bi, Q.
Summary: Xanthomas are important clinical manifestations of disordered lipid metabolism, which are mostly found in patients with familial hypercholesterolaemia (FH), an inherited disorder that is predominantly caused by mutations in the low‐density lipoprotein receptor gene ( LDLR ). Tuberous and tendinous xanthomas with wide distribution and large size are rare; however, they may indicate the severity of FH, and tend to be found in homozygous FH. In this study, we investigated the clinical and genetic aspects of a young patient with FH presenting with multiple large masses in various locations. The lesions on the elbows and buttocks were locally excised and subsequently confirmed by biopsy to be xanthomas. Genetic analysis further confirmed that the patient was compound heterozygous for two mutations in both alleles of the LDLR gene. This rare case of compound heterozygous FH presenting with multiple large and widely distributed xanthomas provides a better understanding of FH and xanthomas.